Relevansi Pemikiran Pendidikan Al-Ghazali Dengan Pendidikan Islam Kontemporer Tentang Keseimbangan Intelektual Dan Spiritual - Mumtaza Zamhariroh, Nazila; Rahmania Azis, Annisa; Ratu Nata, Balqisa; Fahmi, Muhammad; Salik, Mohamad (Kariman: Jurnal Pendidikan Keislaman, 2024)
This article discusses the relevance of Al-Ghazali's educational thought in the context of modern Islamic education, focusing on the balance between intellectual and spiritual aspects. In the face of issues currently confronting Islamic education, such as moral crises, the influence of globalization, and tendencies toward secularism, this research aims to highlight how Al-Ghazali's educational concepts can offer effective solutions. This is a kind of qualitative research method with a literature study approach. The data analysis technique used is content analysis, including Al-Ghazali's works and contemporary writings on Islamic education.  The study’s results indicate that Al-Ghazali emphasizes the importance of balancing intellectual and spiritual development to produce intelligent and moral individuals capable of facing modern challenges. His thought not only strengthens the integration of knowledge and religion but also equips younger generations with the character and ethics necessary to navigate the complexities of the modern world. Thus, Al-Ghazali's ideas are highly significant and relevant to developing a quality, competitive Islamic education.